Length of Stay Children Hospitalized with Chronic Kidney Disease Based on Etiology and Stage in Dr. Hasan Sadikin Hospital Bandung - Angelreika Libowo; Ahmedz Widiasta; Dedi Rachmadi (Faculty of Medicine Universitas Padjadjaran, 2020)
Objectives: This study aims to describe the LOS children hospitalized with CKD based on the etiology and stage at Dr. Hasan Sadikin General Hospital, Bandung in 2016–2018.Methods: This was a retrospective study with a cross-sectional design from June–October 2019. The inclusion were all medical records of pediatric inpatient diagnosed with CKD and exclusion criteria were incomplete medical record data and hospital readmission patients. The variables studied were CKD etiology, CKD stage, and length of stayResults: From 103 patients, the etiologies found were steroid-resistant nephrotic syndrome (SRNS) (58.25%), congenital anomalies of kidney and urinary tract (9.71%), urinary tract infection (5.83%), and chronic glomerulonephritis (21.36%). The mean LOS was 19 days. The longest LOS found in CKD stage 5 patients caused by SRNS (141 days). Meanwhile, the shortest LOS was found in CKD stage 2 patients caused by chronic glomerulonephritis and CKD stage 5 patients were caused by SRNS who died (1 day). Conclusion: Pediatric patients with CKD stage 5 with SRNS has the potential to have a longer LOS than other etiologies.